A successful approach for angiosarcoma of the scalp using helical tomotherapy and customized surface mold brachytherapy: A case report. Issue 49 (10th December 2021) - Suzuki, Gen; Masui, Koji; Watanabe, Sho; Yamazaki, Hideya; Takenaka, Tadashi; Asai, Jun; Maruyama, Ayano; Yamada, Kei
Abstract: Rationale: Angiosarcoma of the scalp (ASS) is a rare solid tumor with a high risk of local recurrence. Effective treatment strategies are not currently available for angiosarcoma of the scalp (ASS). The aim of this study was to report the utility of high-dose-rate brachytherapy (HDRBT) as a boost treatment for ASS following total scalp irradiation using helical tomotherapy (HT). This is the first report of successful treatment of ASS using HT and HDRBT. Patient concerns: An 81-year-old woman presented with hemorrhagic nodular skin tumors of the scalp. The patient first noticed the scalp mass 3 months before consultation, which became significantly enlarged within a short period. The tumor was positioned mostly in the parietal area, although the skin color change was widely spread to the surrounding scalp. Diagnosis: The patient underwent biopsy of the skin lesion at the right parietal region, which revealed the presence of angiosarcoma on pathological examination. There was neither regional lymphadenopathy nor distant metastases on PET/CT. Interventions: Considering the patient's old age and poor performance status because of a history of cerebral infarction, we considered that she was eligible for definitive chemoradiotherapy of the scalp. We adopted an individual surface mold HDRBT boost of 18 Gy in three fractions following total scalp irradiation with 50 Gy in 25 fractions delivered using HT. Docetaxel (40 mg/m 2 ) was administered every 4 weeks, concurrently with radiotherapy. Outcomes: Treatment tolerance was good, and severe toxicity has not been observed to date. At 18 months after radiotherapy, the patient does not have any evidence of recurrence. Conclusion: Customized surface mold HDRBT following total scalp irradiation using HT resulted in excellent disease control and minimal toxicity; thus, it may be a promising therapeutic option for ASS.